Evaluation of Spinning Cone Column Distillation as a Strategy for Remediation of Smoke Taint in Juice and Wine - Carolyn Puglisi; Renata Ristic; Jamie Saint; Kerry Wilkinson (Molecules, 2022)
Where vineyard exposure to bushfire smoke cannot be avoided or prevented, grape and wine producers need strategies to transform smoke-affected juice and wine into saleable product. This study evaluated the potential for spinning cone column (SCC) distillation to be used for the remediation of ‘smoke taint’. Compositional analysis of ‘stripped wine’ and condensate collected during SCC treatment of two smoke-tainted red wines indicated limited, if any, removal of volatile phenols, while their non-volatile glycoconjugates were concentrated due to water and ethanol removal. Together with the removal of desirable volatile aroma compounds, this enhanced the perception of smoke-related sensory attributes; i.e., smoke taint intensified. Stripped wines also became increasingly sour and salty as ethanol (and water) were progressively removed. A preliminary juice remediation trial yielded more promising results. While clarification, heating, evaporation, deionization and fermentation processes applied to smoke-tainted white juice gave ≤3 µg/L changes in volatile phenol concentrations, SCC distillation of smoke-tainted red juice increased the volatile phenol content of condensate (in some cases by 3- to 4-fold). Deionization of the resulting condensate removed 75 µg/L of volatile phenols, but fermentation of reconstituted juice increased volatile phenol concentrations again, presumably due to yeast metabolism of glycoconjugate precursors. Research findings suggest SCC distillation alone cannot remediate smoke taint, but used in combination with adsorbents, SCC may offer a novel remediation strategy, especially for tainted juice.